1991
DOI: 10.1007/bf01000381
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of myelin gene expression in SV40 T antigen-transfected rat glioma C6 cells

Abstract: Rat glioma C6 cells were stably transfected with a pSV3-neo plasmid containing SV40 T antigen gene, and geniticin-resistant transfectants (designated C6T cells) were cloned. The C6T cells grew as well-defined foci of cells showing squamous or irregular morphology. The doubling time for transfected cells was reduced by approximately 40% as compared to control C6 cells. The transfection with T-antigen also affected the expression of genes coding for structural myelin proteins and for myelin-associated enzymes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Early passage C6 cells used in this study express low amounts of the MAG mRNA (Bong et al, 1991;Kanoh et al, 1991), but when normalized to the total RNA it is only approximately one three hundredth of that in oligodendrocytes (Konat, unpublished observation). The MAG gene expression in C6 cells can be upregulated approximately 50-fold by treatment with CAMP potentiator, i.e., isoproterenol (Ye et al, 1992(Ye et al, , 1994.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Early passage C6 cells used in this study express low amounts of the MAG mRNA (Bong et al, 1991;Kanoh et al, 1991), but when normalized to the total RNA it is only approximately one three hundredth of that in oligodendrocytes (Konat, unpublished observation). The MAG gene expression in C6 cells can be upregulated approximately 50-fold by treatment with CAMP potentiator, i.e., isoproterenol (Ye et al, 1992(Ye et al, , 1994.…”
Section: Resultsmentioning
confidence: 98%
“…In the actively myelinating brain employed in this study (25-30 day postpartum), the gene activity normalized to the total RNA was about four fold lower than in purified oligodendrocytes, which approximately reflects the proportion of oligodendrocytes within cellular population of the tissue. Early passage C6 cells used in this study express low amounts of the MAG mRNA (Bong et al, 1991;Kanoh et al, 1991), but when normalized to the total RNA it is only approximately one three hundredth of that in oligodendrocytes (Konat, unpublished observation). The MAG gene expression in C6 cells can be upregulated approximately 50-fold by treatment with CAMP potentiator, i.e., isoproterenol (Ye et al, 1992(Ye et al, , 1994.…”
Section: Resultsmentioning
confidence: 99%
“…The aim of this study was to evaluate possible involvement of cAMP in the regulation of PLP and myelinassociated glycoprotein (MAG) gene expression in rat glioma C6 cells. These cells express several myelin-specific genes, namely, CNP, PLP and MAG, and the expression can be experimentally modified (McMoms, 1983;McMorris et al, 1985;Bong et al, 1991;Konat et al, 1991b;Nave and Lemke, 1991). Since isoproterenol, a P-adrenergic receptor agonist, transiently increases cAMP level in C6 cells (Gilman and Nirenberg,197 1 ; Sharma and Raj , 1987), we employed it as a model drug along with propranolol, a P-antagonist, and forskolin, an adenylate cyclase activator.…”
mentioning
confidence: 99%
“…Several studies showed that MBP synthesis were inhibited by the overexpression of SV40‐Tag at various levels (Tennekoon et al . 1987; Bong et al . 1991; Verity et al .…”
Section: Discussionmentioning
confidence: 99%